Structural Basis of Potential Inhibitors Targeting SARS-CoV-2 Main Protease - Mengist, Hylemariam Mihiretie; Dilnessa, Tebelay; Jin, Tengchuan (Frontiers in Chemistry, 2021)
The Coronavirus disease-19 (COVID-19) pandemic is still ravaging the world causing significant social, economic, and political chaos. Corresponding to the absence of globally approved antiviral drugs for treating and vaccines for controlling the pandemic, the number of cases and/or mortalities is unintendedly rising. Current patient management relies on supportive treatment and the use of repurposed drugs as an indispensable option. Of its crucial role in the viral life cycle, ongoing studies are looking for potential inhibitors to the main protease (Mpro) of severe acute respiratory syndrome Coronavirus -2 (SARS-CoV-2) to tackle the pandemic. Although promising results have been achieved in searching for drugs inhibiting the Mpro, there are remaining works on the structure-based designing of improved drugs. This review discusses the structural basis of potential inhibitors targeting SARS-CoV-2 Mpro, identify gaps, and forward future directions. Further, compounds with potential Mpro based antiviral activity are highlighted.